Critical Discourse Analysis of Sinhala Cultural Identity in Celebrity Endorsement in Newspaper Advertisements - Jayasingha, S.M.; Shivany, S. (Research gate, 2018)
Advertisements play major role in unfirming product and services to the market. Celebrity endorser as any individual who relished public credit and who uses recognition on behalf of a consumer good by appearing with it in an advertisement. In today’s media cluttered environment where it is difficulty to grab consumer’s attention. Celebrities develop a person through the type of roles they play in society as well as how they are portrayed in the media. When celebrities endorse a product, the meaning developed around a particular celebrity will transfer to a company, brand, or product. This study examined printed image advertisements via Critical Discourse Analysis perspective. This study mainly focused on the Sinhala cultural identity in celebrity endorsements employed by advertisers to influence their customers. This research followed Fairclough’s threedimensional framework. It demonstrates how the ideology of ‘cultural identity’ is produced and reproduced through advertisements in popular printed advertisement materials. A qualitative critical discourse analysis was done on 25 newspaper advertisements. Finding indicated that advertisers used various strategies to reach the consumers through cultural identity. The advertisements, which promote Sinhala cultural identity, norms and influence customers to a certain extent into believing whatever that is advertised is undeniably true. This study revealed that the Sinhala cultural identity was considered as an advertising strategy by few producers for positioning their products. Finding showed that cultural celebrity commendations as a means to exercise control over the unique culture, but it can be seen in few advertisements, but it is recommended that the producers and providers of services should consider the celebrity features, which set with the culture of the consumer, to whom the company targets.
Keywords: Critical discourse analysis; Cultural endorsement; Sinhala cultural identity.